Les deux justices selon Nietzsche : un exemple d’inversion des valeurs - Arnaud François (Meta: Research in Hermeneutics, Phenomenology and Practical Philosophy, 2009)
There are two types of justice in Nietzsche: a moral justice that he criticizes and an extra-moral one which corresponds to a « a great justice » that he sustains. However, in the passage from the former to the latter concept, it can be clearly seen what Nietzsche calls a « shift in values », that is not a simple inversion between the top and the bottom, but a substitution from a gradual, hierarchical conception of values to a binary or dualist one. Thus, a third Nietzschean concept of justice can be identified; this is the most original and important of all and refers to this hierarchy and its acknowledgement.